Genome-wide analysis of the CAD gene family reveals two bona fide CAD genes in oil palm - Chong, Yusuf Yu Lok; Sabri, Nuraini Nabilah; Mohd Taufik, Nur Atiqah Amiza; Abu Seman, Idris; Abdullah, Mohd Puad (Springer, 2022)
Cinnamyl alcohol dehydrogenase (CAD) is the key enzyme for lignin biosynthesis in plants. In this study, genome-wide analysis was performed to identify CAD genes in oil palm (Elaeis guineensis). Phylogenetic analysis was then conducted to select the bona fide EgCADs. The bona fide EgCAD genes and their respective 5′ flanking regions were cloned and analysed. Their expression profiles were evaluated in various organs using RT-PCR. Seven EgCAD genes (EgCAD1-7) were identified and divided into four phylogenetic groups. EgCAD1 and EgCAD2 display high sequence similarities with other bona fide CADs and possess all the signature motifs of the bona fide CAD. They also display similar 3D protein structures. Gene expression analysis showed that EgCAD1 was expressed most abundantly in the root tissues, while EgCAD2 was expressed constitutively in all the tissues studied. EgCAD1 possesses only one transcription start site, while EgCAD2 has five. Interestingly, a TC microsatellite was found in the 5′ flanking region of EgCAD2. The 5′ flanking regions of EgCAD1 and EgCAD2 contain lignin-associated regulatory elements i.e. AC-elements, and other defence-related motifs, including W-box, GT-1 motif and CGTCA-motif. Altogether, these results imply that EgCAD1 and EgCAD2 are bona fide CAD involved in lignin biosynthesis during the normal development of oil palm and in response to stresses. Our findings shed some light on the roles of the bona fide CAD genes in oil palm and pave the way for manipulating lignin content in oil palm through a genetic approach.